Detection Metbod of Trojan's Control Domain Based on Improved Neural Network Algoritbm - Aijiang Liu; Changhui Huang; Guangjun Hu (Dianxin kexue)
Firstly, the character that the Trojans use domain name to control was analyzed and the method that DNS adopted to detect Trojans was introduced. Secondly, based on the analysis of static and dynamic characters for Trojan domain name, eight indicators were obtained as the input of BP neural network algorithm, including operation time of domain name, the period to visit the domain name, the variation speed of IP address, the country change of IP address, IP address of private address, the same domain name with multiple IP address for different countries, TTL value and search times of domain name. An improved BP neural network algorithm was proposed to solve training efficiency for a great number of domain names, and large average error. Finally, the experimental evaluation of samples was tested by improved neural network algorithm. Compared with traditional neural network algorithm, the detection efficiency is better.